Disintegrant activities of natural and pregelatinized trifoliate yams, rice and corn starches in paracetamol tablets - Musiliu O. Adedokun, Oludele A. Itiola (Journal of Applied Pharmaceutical Science)
Natural and pregelatinized starches from white and yellow trifoliate yams and rice were comparatively studied with official corn starch, in a paracetamol tablet formulation to assess their relative effectiveness as disintegrants. Disintegration time (Dt) and the (crushing strength/friability)/disintegration time ratio (Cs/Fr)/Dt were employed as assessment parameters. Generally, the rankings of (Cs/Fr)/Dt for the natural and pregelatinized starch disintegrants were white T. yam > corn > yellow T. yam > rice; and white T. yam > yellow T. yam > corn > rice, respectively. Pregelatinized starches produced better combined disintegrant properties of (Cs/Fr)/Dt than natural starches. Tablets formulated with official corn starch disintegrant exhibited the lowest disintegration time values, but generally all the tablets containing the experimental starches also passed the official disintegration time test, and can therefore be used as alternative disintegrants in tablets.
Keywords: Disintegrants, natural starch, pregelatinized starch, trifoliate yams, rice.